(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This research aimed to isolate and identified the pathogen caused wilt in pumpkin plants and control by two bioformulation Trichoderma harzianum and Pseudomonas fluorescens. The results revealed that the caused pathogen of pumpkin wilt plants was Fusarium oxysporum which diagnosis has been confirmed by using PCR Technique. The results of pathogenesity revealed that 60.17% from Plants grown in contaminated soil infected with F. oxysporum. Also the results showed that use the T. harzianum that has high antagonism with pathogen, the degree of antagonism has reached 2 with F. oxysporum at Bell scale. P. fluorescens showed inhibition ratio against F. oxysporum and T. harzianum. reached 44 and 27% respectively. The results with use antibiosis for T. harzianum , P. fluroescens and manure revealed that the least severity was in the transactions MThPf (manure, fungi and Bacteria), MTh (manure and fungi), ThPf (fungi and bacteria), Th (T. harzianum), Pf (P. fluorescens), MPf (manure and bacteria), where ranged 0 - 5.56% , which did not differ significantly between them compared to M (manure) and control that reached 13.69% and 22.22% respectively. Weight in soil contaminated with pathogen in MThPf and ThPf that reached 376.83 and 379.22gr compard with control in the same soil when reached 66.41 gr .The results of the analysis with used GCMas revealed transactions in presence of Antibiotics and substances Phenol 2,5-bis (1,1-dimethyl), 4-Fluorobenzyl alcohol, Hexadecanoic acid (2) -methyl ester, 1-Pyrrolidine butanoic acid, gamma-Tocophenol and 9-Octanoic acid (2) -2-hydrox.